Determinants of Adolescents Pregnancy and the Incidence of Stunting in Children 24-59 Months of Age - Didien Ika Setyarini; Reni Wahyu Triningsih; Hening Ryan Aryani; Dwi Estuning Rahayu (STIKes Patria Husada Blitar, 2026)
Adolescent pregnancy is a significant public health issue that can lead to various adverse outcomes, including stunting in children. This study aims to investigate the determinants of adolescent pregnancy and their association with the incidence of stunting in children aged 24-59 months at Poncokusumo Health Center, Malang Regency. The research employs a cross-sectional design, collecting primary data through interviews and secondary data from the Puskesmas Poncokusumo. The study includes 93 mothers of stunted toddlers with a history of adolescent pregnancy. The sampling technique used purposive sampling. Data were analyzed by chi-square.The analysis reveals significant relationships between educational level economic status, knowledge, the role of healthcare providers, and family support with the incidence of stunting, while employment status shows no significant correlation. The findings suggest that targeted interventions addressing these determinants could mitigate stunting rates among children born to adolescent mothers. Further research should explore the psychosocial impacts and long-term outcomes for these children, as well as the effectiveness of existing healthcare interventions